Adaptive process control for turning operation using expert systems. (15th October 2008) - Gopalakrishnan, Bhaskaran; McCoy, Meredith L.
Process control is concerned with the reduction of variance in the key aspects of a process. Process control is practiced in a variety of industries, including the chemical, petroleum, pharmaceutical, glass, steel and electric power generation industries. Traditional systems still have difficulty dealing with the non-linear nature of various processes, the vagueness of information about the process and the rapidly changing nature of the information about the process. Expert systems have the capacity to solve these problems because of their ability to process information with real time updating, deal with uncertain or incomplete knowledge, incorporate new knowledge into the program easily and put less pressure and responsibility on the human operator. This paper demonstrates the use of expert systems in process control using a realistic example and evaluates the effect of different manufacturing parameters.